An exploration of reading strategies employed by grade 12 learners in Modjadji Circuit, Limpopo Province : towards developing reading intervention strategies in English First Language - Modipane, Makgomo Christina (My University, 2022)
This study explored the reading strategies employed by Grade 12 learners in Modjadji Circuit, Limpopo Province: Towards developing an intervention reading strategies in English First Additional Language. The research was undertaken in one public secondary school. The researcher focused on Grade 12 learners of the mentioned circuit. The study followed the qualitative approach, and a case study research design was selected. Interviews were conducted with 12 learners and three teachers who were purposively selected from one public school. Document analysis and observations were also used to collect data. The findings of the study showed that learners and educators employ reading strategies during the reading of English text. Learners employ the reading strategies to enhance their reading ability and to improve their reading skills. The following different reading strategies were found to be used, namely, activating background knowledge, main ideas, summarising, visualising, predicting, inferencing, questioning, monitoring-clarifying extensive strategy, intensive strategy, pre-reading, during- reading, post-reading, and peer-assisted strategy. It was also found that most learners experience problem of decoding English words correctly and that teachers always assist them to decode them well during reading. It was found that documents such as subject policy, school policy and school-time-table do not provide guidance on how to teach reading. The documents do not also guide teachers on how to implement reading strategies. The study recommends that the school time-table should consider including reading periods on the time table. All the mentioned policies above should provide guidance on how to implement reading strategies. The Department Of Education should encourage all schools to participate in a “Drop All and Read” competition. The study recommend that teachers employ different reading strategies to teach reading. Learners must also employ various reading strategies to improve their reading skills and to enhance their reading ability.
Thesis (Ph.D. (Education)) -- University of Limpopo, 2022
Keywords: Reading strategies; Grade 12 learners; Modjadji Circuit; Limpopo Province; Reading skills improvement; English First Additional Language; Reading -- Ability testing -- South Africa -- Limpopo; Reading (Secondary) -- South Africa; Reading (Secondary) -- Ability testing; English language -- Ability testing -- South Africa; Reading Skills Competency Tests